2001
DOI: 10.1038/sj.bjp.0704306
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ca2+ release induced by clofibric acid from the sarcoplasmic reticulum of mouse skeletal muscle fibres

Abstract: To characterize the effect of clofibric acid (Clof) on the Ca2+ release mechanism in the sarcoplasmic reticulum (SR) of skeletal muscle, we analysed the properties of Clof‐induced Ca2+ release under various conditions using chemically skinned skeletal muscle fibres of the mouse. Clof (>0.5 mM) released Ca2+ from the SR under Ca2+‐free conditions buffered with 10 mM EGTA (pCa >8). Co‐application of ryanodine and Clof at pCa >8 but not ryanodine alone reduced the Ca2+ uptake capacity of the SR. Thus, Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Recently, it was reported that clofibrate-induced myopathy is related to carcium influx (Ikemoto and Endo, 2001;Matzno et al, 2006). Hodel briefly reviewed clofibrate-induced 520 OKADA ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that clofibrate-induced myopathy is related to carcium influx (Ikemoto and Endo, 2001;Matzno et al, 2006). Hodel briefly reviewed clofibrate-induced 520 OKADA ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…D-tubocurarine chloride was purchased from Nacalai Tesque, Inc. All the other chemicals were as described in the previous paper (Ikemoto & Endo, 2001, accompanying study).…”
Section: Other Materialsmentioning
confidence: 99%
“…The muscle preparation was immersed in PSS. Preparation of skinned ®bres was described previously (Ikemoto & Endo, 2001, accompanying study). All experiments were carried out at room temperature (21 ± 238C).…”
Section: Preparation Of Muscle Fibresmentioning
confidence: 99%
See 2 more Smart Citations